Leveraging PDS teacher preparation grants: a majority-minority research university's approach to increasing the diverse teacher pipeline - Joseph R. Feinberg; Yasmine Bey (Emerald Publishing, 2024)
Purpose - A primary goal of the Collaboration and Resources for Encouraging and Supporting Transformations in Education (CREST-Ed) program was to increase the number of highly qualified, minoritized teachers committed to teaching in minority-serving, high-need school districts. This study's purpose was to evaluate the CREST-Ed program's impact on teacher residency outcomes using multiple sources of program evaluation data collected during the five-year grant. Design/methodology/approach - This study of a federal Teacher Quality Partnership (TQP) grant at Georgia State University (GSU), a minority-serving institution (MSI) and research university, shows teacher residency programs can improve the diverse teacher pipeline. The grant, CREST-Ed, provided professional development schools (PDS) support for four urban and 23 rural school districts through partnerships with GSU, Albany State University (ASU) and Columbus State University (CSU). Findings - The study findings suggest that teacher preparation grants can be leveraged to recruit traditionally minoritized teachers of color to increase the diverse teacher pipeline and strengthen PDS partnerships. Originality/value - Both urban and rural PDSs could benefit from teacher residency programs like the CREST-Ed model that catered to the unique needs of each school and partnership district.